2016
DOI: 10.1155/2016/2196703
|View full text |Cite
|
Sign up to set email alerts
|

Low Level of Microsatellite Instability Correlates with Poor Clinical Prognosis in Stage II Colorectal Cancer Patients

Abstract: The influence of microsatellite instability (MSI) on the prognosis of colorectal cancer (CRC) requires more investigation. We assessed the role of MSI status in survival of individuals diagnosed with primary colorectal cancer. In this retrospective cross-sectional study the MSI status was determined in 158 formalin-fixed paraffin-embedded tumors and their matched normal tissues from patients who underwent curative surgery. Cox proportional hazard modeling was performed to assess the clinical prognostic signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 43 publications
6
27
2
2
Order By: Relevance
“…In hereditary non-polyposis colorectal cancer (HNPCC) the cause is germ line mutation in one of the DNA mismatch repair genes, and MSI was a potential screening tool for HNPCC. So consistent with previous studies (16,19), MSI status was found to be associated with family history. CEA is the most routinely used colorectal tumor marker, and is recommended by the National Academy of Clinical Biochemistry and American Society of Clinical Oncology for prognosis, monitoring response to treatment and disease recurrence (20,21).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In hereditary non-polyposis colorectal cancer (HNPCC) the cause is germ line mutation in one of the DNA mismatch repair genes, and MSI was a potential screening tool for HNPCC. So consistent with previous studies (16,19), MSI status was found to be associated with family history. CEA is the most routinely used colorectal tumor marker, and is recommended by the National Academy of Clinical Biochemistry and American Society of Clinical Oncology for prognosis, monitoring response to treatment and disease recurrence (20,21).…”
Section: Discussionsupporting
confidence: 92%
“…The prognostic significance of MSI for patients with colorectal cancer is a subject of controversy. Some investigations reported that patients with MSI-H tumors had a better prognosis than those with MSI-L or MSS tumors (15,16), while others reported that MSI in colorectal cancer was not an independent prognostic factor (17,18). From previous studies, poor differentiation showed a trend in favor of a shorter survival for patients, but not significantly (8,15).…”
Section: Discussionmentioning
confidence: 99%
“…An explanation for this diversity may be related to the fact that we did not include ANTICANCER RESEARCH 37: 2011-2018 (2017) 2016 stage IV patients in our cohort. Therefore, the SNP rs13347 may actually be of different prognostic value in adjuvant versus metastatic situations analogous to the role of microsatellite instability status in distinct colorectal cancer stages (30). A limitation of our study is its retrospective design; therefore, a selection bias cannot be fully excluded.…”
Section: Discussionmentioning
confidence: 93%
“…MSI analysis was performed using a panel of three mononucleotide markers: BAT‐25, BAT‐26, and NR‐27 and EMAST analysis was performed using a panel of five tetranucleotide markers: D20S82, D20S85, D9S242, D8S321, and MYCL1. Polymerase chain reaction (PCR) was performed with previously described primers (Mojarad et al, ; M. M. Watson et al, ) without fluorescent labels. Amplification reactions (25 μl) were prepared subjected to PCR amplification: Initial incubation at 95°C for 5 min, followed by 35 cycles of 95°C for 40 s, 62°C for 40 s, and 72°C for 40 s, and a final incubation at 72°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%